Pneumonia: Features registered in autopsy material. Issue 4 (4th July 2017) - Kosjerina, Zdravko; Vukoja, Marija; Vuckovic, Dejan; Kosjerina Ostric, Vesna; Jevtic, Marija
Abstract : Background : Despite improvements in clinical practice, pneumonia remains one of the leading causes of death worldwide. Pathologic findings from autopsy reports could provide more precise and valid data on characteristics of pneumonia patients. Methods : We retrospectively reviewed autopsy reports of deceased patients admitted to the Institute for Pulmonary Diseases of Vojvodina in Sremska Kamenica, Serbia, between 1994 and 2003. The patients were classified into two groups: group 1 ( n = 161) comprised patients in whom pneumonia was the main cause of death, while group 2 ( n = 165) consisted of patients in whom pneumonia was confirmed at autopsy but had various different causes of death. Results : From 1776 patients who underwent autopsy 326 (18.3%) were diagnosed with pneumonia. The most common underlying diseases were atherosclerosis (29.4%), chronic obstructive pulmonary disease (COPD) (26.7%), and malignancies (20.2%). Pneumonia was the main cause of death in 161 cases (group 1) while in group 2 major causes of death were heart failure (HF) (26.7%), acute myocardial infarction (AMI) (16.4%), and pulmonary embolism (PE) (10.9%). Multilobar involvement (91% vs.27%), pulmonary effusion (29% vs.14%), and lung abscess (23.6% vs.8.5%) were more frequently found in group 1, compared to group 2. Conclusion : In patients with pneumonia who underwent autopsy most common underlying diseases were atherosclerosis, COPD, and malignancies, while major causes of death were: progression of pneumonia, HF, AMI, and PE.